A VSG Power Decoupling Control with Integrated Voltage Compensation Schemes - Longhai Wei; Bo Yang; Shuai Lu (Energies)
Virtual synchronous generator (VSG) control enables grid-connected power electronic converters to retain the inertia support and frequency stability features of traditional synchronous generators in power grids. The power coupling of VSG remains a major issue, where reactive power deviates from the commands. Numerous existing VSG decoupling methods essentially focus on applying virtual impedances in different ways to alter the equivalent line impedance ratio. These methods are less effective under varying operating points. To address the problem, the voltage compensation term from virtual resistance and inductance is first made adaptive to varying operating points through the proposed online parameters’ adjustment. Then, it is further discovered that it is still not possible to achieve total power decoupling for the full operating range. Therefore, an additional voltage compensation term, in terms of the power angle variations, is proposed to eliminate the power coupling at high power ranges. The two proposed voltage compensation schemes are seamlessly integrated so that total VSG power decoupling can be achieved. Through comparative lab tests with existing methods, it is validated that the proposed method is more effective in eliminating reactive power coupling under varying and high-power operating points during both steady and transient states.